PENINGKATAN KETERAMPILAN MEMBACA PUISI SISWA KELAS IV DENGAN MODEL DEMONSTRASI DIDUKUNG MEDIA VIDEO PEMBELAJARAN DI SDN 1 SUMBERSARI KOTA MALANG - Sari, Yolanda Dana Kumala; Chamisijatin, Lise; Santoso, Budi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study is to improve poetry reading skill of 4th grade students at SDN Sumbersari 1 in Malang City, to know the activities of the teacher and students. This type of this research is classroom action research. This classroom action research model uses the Kemmis & Mc Taggart model which consist of four steps or stages in conducting classroom action research, namely: planning, action, observation, and reflection. The result of the study show an increasing activity of the teacher and students. The result of this study are flows. (1) Pre-action, from 25 students, only 5 students or 20% of the total students are able to read poetry well and correctly, while 20 students or 80% of students experience difficulty in reading poetry with an average poetry reading skill of 54.56%. (2) Cycle I, the percentage of teacher activity reached 83% with very good predicate, the percentage of teacher activity reached 83% with very good predicate, the percentage of student activity was 83% with very good predicate, and classical learning completeness was 78.8% (3) Cycle II, the percentage of teacher activity reached 86% with very good predicate, the percentage of students is 87% with